A novel herbal formulation in the management of diabetes - Bhujbal, Santosh S; Hadawale, Sunita S; Kulkarni, Parag A; Bidkar, Jayant S; Thatte, Vidya A; Providencia, Clarine A; Yeola, Rupesh R (International Journal of Pharmaceutical Investigation)
Background and Aim: Momordica charantia Linn. is traditionally used as a medicine for diabetes. The present investigation was aimed to formulate and evaluate transdermal patchesof Momordica charantia Linn. Materials and Methods: The transdermal films containing the herbal drug component fractionated fromethanolicextract of M. charantia fruits were prepared by using hydroxy propyl methyl cellulose as a polymer.The films were evaluated for folding endurance, thickness, weight variation, drug contents and in vitro diffusion studies and in vivo parameterslike acute and sub-acute antihyperglycemic activity in diabetic rats, biochemicalstudies, skin irritation in rats and stability studies. Result and discussion: The weightof transdermal patches of M. charantia (2 cm2; 10 mg/patch) and was found to be 0.03 gm.Thickness of patches of M. charantia (2 cm2; 10 mg/patch) was found to be satisfactory. The percentage release of active constituents from transdermal patches of M.charantia (2 cm2; 10 mg/patch) was found to be 47.59% in 10% hydroalcoholic phosphate buffer pH 7.4 at the end of 6 h. The transdermal route exhibited negligible skin irritation and in vivo results revealed that the patches successfully decrease the blood glucose level. Conclusion: From the results, we concluded that the well-known herbal drug M. charantia Linn. have been found to be effective for diabetes through modern pharmaceutical formulation techniques.
Keywords: Diabetes mellitus; diethyl ether fraction; M. charantia Linn; transdermal patch